A protocol for rapid generation cycling (speed breeding) of hemp (Cannabis sativa) for research and agriculture. (20th December 2022) - Schilling, Susanne; Melzer, Rainer; Dowling, Caroline A.; Shi, Jiaqi; Muldoon, Shaun; McCabe, Paul F.
SUMMARY: Hemp ( Cannabis sativa ) is a highly versatile crop with a multitude of applications, from textiles, biofuel and building material to high‐value food products for consumer markets. Furthermore, non‐hallucinogenic cannabinoids like cannabidiol (CBD), which can be extracted from female hemp flowers, are potentially valuable pharmacological compounds. In addition, hemp has high carbon sequestration potential associated with its rapid growth rate. Therefore, the hemp industry is gaining more traction and breeding hemp cultivars adapted to local climate conditions or bred for specific applications is becoming increasingly important. Here, we present a method for the rapid generation cycling (speed breeding) of hemp. The speed breeding protocol makes use of the photoperiod sensitivity of Cannabis . It encompasses vegetative growth of the plants for 2 weeks under continuous light, followed by 4 weeks under short‐day conditions, during which flower induction, pollination and seed development proceed, and finally a seed ripening phase under continuous light and water stress. With the protocol described here, a generation time of under 9 weeks (61 days) from seed to seed can be achieved. Furthermore, our method synchronises the flowering time of different hemp cultivars, thus facilitating crosses between cultivars. The extremely short generation time will enable hemp researchers and breeders to perform crosses in a time‐efficient way and generate new hemp cultivars with defined genetic characteristics over a short period of time. Significance Statement: Shortening crop generation times accelerates plant breeding and research. Here we present a speed breeding protocol for hemp ( Cannabis sativa ) that enables the growth of five generations in 1 year.